2002
DOI: 10.1109/3477.990881
|View full text |Cite
|
Sign up to set email alerts
|

Analytical structures and analysis of the simplest fuzzy PD controllers

Abstract: This paper deals with simplest fuzzy PD controllers which employ only two fuzzy sets on the universe of discourse of each input variable, and three fuzzy sets on the universe of discourse of output variable. First, analytical structures of the simplest fuzzy PD controllers are derived via triangular membership functions for fuzzification, intersection T-norm, Lukasiewicz OR and Zadeh (1965) OR T-conorms, Mamdani's minimum, Larsen's product and drastic product inference methods, and center of area method for de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 14 publications
0
20
0
Order By: Relevance
“…The nature of this issue is the same as when deriving the analytical structure of the T1-FLCs whose fuzzy rules involve the Zadeh AND operator [29,30]. We consider the case, when E * (k) is inside [− L 1 − P 1 , L 1 + P 1 ], and V * (k) is inside [− L 2 − P 2 , L 2 + P 2 ] for brevity.…”
Section: Analytical Structure Of the Interval Type-2 Fuzzy Pid Contromentioning
confidence: 98%
See 2 more Smart Citations
“…The nature of this issue is the same as when deriving the analytical structure of the T1-FLCs whose fuzzy rules involve the Zadeh AND operator [29,30]. We consider the case, when E * (k) is inside [− L 1 − P 1 , L 1 + P 1 ], and V * (k) is inside [− L 2 − P 2 , L 2 + P 2 ] for brevity.…”
Section: Analytical Structure Of the Interval Type-2 Fuzzy Pid Contromentioning
confidence: 98%
“…As shown in Eqs. (25), (29) and (33), the IT2F-PID is a nonlinear PID type controller because its structure is the same as the discrete form of the linear PID controller. The controller gains are composed of the IT2F-PID parameters G e1 , G v1 , G e2 , G v2 , G u and G u .…”
Section: Remarkmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the above, the fuzzy PID pacing rate is then defuzzified using the standard center of area (COA) method [37] yielding the subsequent pacing rate provided by the pacemaker and applied on the heart corresponding to the current actual heart rate.…”
Section: Fpid Control Rules and Membership Functionsmentioning
confidence: 99%
“…It has been shown that a fuzzy controller can be very effective for controlling a system of unknown structure and nonlinear behavior [4] [5] . In this paper, both conventional PID and fuzzy PI [6] control algorithm have been applied for controller design. Fuzzy PI control resulted in better control performance.…”
Section: Introductionmentioning
confidence: 99%